Partnerships in Teacher Education – Going Beyond the Rhetoric, with Reference to the Norwegian Context - Kari Smith (Center for Educational Policy Studies Journal)
Teacher education plays a central role in education and relates to various stakeholders of education. Currently, teacher education is not perceived as the sole responsibility of higher education institutions, and they are expected to work closely together with other partners. In this paper, the concept of ‘partnership’ is defined and mutual benefits and challenges in partnerships with disciplines and institutions beyond teacher education programs are briefly discussed. Issues related to partnerships with students are addressed, and the last part of the paper discusses the partnership between teacher education and the practice field with examples from Norway. Three models illustrating such partnerships are described. The central argument of the paper is that partnerships in teacher education need to go beyond rhetoric.